2021
DOI: 10.5468/ogs.20264
|View full text |Cite
|
Sign up to set email alerts
|

Social determinants of mental health of women living in slum: a systematic review

Abstract: With the rise of urbanization globally, the problem of living in slums has become a problem for the civil society. As a vulnerable segment, women make up half of the population in these regions; therefore, women's mental health has always been a concern. The purpose of this study was to review the social determinants of mental health in women living in slum areas. Methods We systematically reviewed articles published between 2009 and 2019 on the social determinants of women's mental health in SID, Magiran, Goo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 34 publications
2
5
0
Order By: Relevance
“…Inequalities in the distribution of doctor diagnosed and screened depression are stark. The findings echo those of earlier research in Brazil and internationally, which shows female sex, increased age, comorbidities, and smoking are associated with increased odds of depression (Wittayanukorn et al, 2014;Stopa et al, 2015;Souza Lopes et al, 2016;Abdi et al, 2021). Although research has not determined a definitive cause for higher rates of depression in women, previous analysis has suggested that higher Gross National Income (GNI) and shifting gender roles can influence the ratio of depression between males and females (Rai et al, 2013).…”
Section: Discussionsupporting
confidence: 86%
“…Inequalities in the distribution of doctor diagnosed and screened depression are stark. The findings echo those of earlier research in Brazil and internationally, which shows female sex, increased age, comorbidities, and smoking are associated with increased odds of depression (Wittayanukorn et al, 2014;Stopa et al, 2015;Souza Lopes et al, 2016;Abdi et al, 2021). Although research has not determined a definitive cause for higher rates of depression in women, previous analysis has suggested that higher Gross National Income (GNI) and shifting gender roles can influence the ratio of depression between males and females (Rai et al, 2013).…”
Section: Discussionsupporting
confidence: 86%
“…Migration costs consist of two main aspects: the rural means of production that need to be given up, and the urban cost of living that need to be borne, which appear even heavier in the context of the lack of social security for employees. Firstly, rural land is not only a means of production but also a means of livelihood [ 15 ]. Therefore, it is easy to produce a tunnel effect, and the tunnel effect at this time can alleviate part of the sense of deprivation.…”
Section: Correlation Analysis Of Income Satisfaction and Mental Healt...mentioning
confidence: 99%
“…This 'othering' of certain communities during COVID-19 has been reported by another study from north India [32] as well as one study from South Africa [50]. This issue is of utmost concern since such communities were already vulnerable to mental health conditions, and the pandemic has brought with it a host of additional stressors [57][58][59].…”
Section: Plos Onementioning
confidence: 78%